The Review of The Grounds of Establishing Copula as a Mode of Existence - ali afzali (حکمت صدرایی, 2016)
In some propositions and in some languages (such as Persian), beside to subject and predict, there is a word known as copula. Many Muslim philosophers have regarded copula as a level of the levels of the existence and therefore as a mode of existence. This theory depends on some grounds, which one of the most important of them is that copula has a real existence. But those grounds have been challenged by some philosophers. In this paper, we explore the view of the defenders and criticizers of those grounds, especially the proof for establishing the real existence of copula. That proof based on the view that the truth of those propositions requires the external existence of every components of the proposition, i.e. subject, predict, and especially copula. But certain philosophers objected that this way of establishing the real existence of copula is incorrect, because of confusing the rules of the subject (or internal world) and object (or external world). If something has mental existence, it is not permissible to conclude its external existence.